Hemodynamic assessment of rupture risk during growth stages in middle cerebral artery aneurysms treated with coiling - Rifaqat Ali; Hana Ihsan Hassan; Aman Sharma; Aashim Dhawan; P. Sharma; Waam Mohammed Taher; Mariem Alwan; Ali Fawzi Al-Hussainy; Mahmood Jasem Jawad; Hiba Mushtaq (Scientific Reports)
Abstract Intracranial aneurysm rupture remains a critical clinical concern, particularly for middle cerebral artery (MCA) aneurysms, where sac volume growth is closely associated with hemodynamic destabilization. This study investigates the effect of aneurysm sac enlargement on key hemodynamic parameters and evaluates the biomechanical efficacy of endovascular coiling using patient-specific computational fluid dynamics (CFD) simulations. A baseline aneurysm geometry (volume = 16 mm3) and two scaled growth models (150% = 24 mm3, 200% = 32 mm3) were subjected to pulsatile flow conditions derived from a physiological inlet profile of a 51-year-old male. Blood rheology was modeled as non-Newtonian using the Casson model, while coiling was represented as a porous medium with a fixed porosity of 0.65. Simulation results showed that aneurysm growth significantly elevated hemodynamic stress markers. Without treatment, peak wall shear stress (WSS) exceeded 120 Pa, average WSS rose above 30 Pa, and average area-weighted WSS (AWSS) during early diastole reached ~ 6200 Pa, especially in intermediate sac sizes. Oscillatory shear index (OSI) peaked at ~ 0.28, and average OSI values increased with volume, indicating high flow instability. In contrast, coiling consistently suppressed these metrics across all volumes: peak WSS fell below 100 Pa, average WSS remained under 5 Pa, and OSI was reduced to below 0.03. AWSS and OSI reductions indicated dampened flow oscillations and reduced biomechanical stress. In conclusion, aneurysm sac growth exacerbates rupture-related hemodynamic conditions, but coiling provides effective stabilization by reducing WSS, AWSS, OSI, and flow complexity.